Theory of Constraints Implications in Marketing. Estonian Cases - Kaarna, Kalev; Miljan, Mait (Ekonomika, 2002)
The theory of Constraints received the most attention in the middle of 1990’s, when the developer of the concept Dr. E. Goldratt published his second book “It’s Not Luck”. In spite of impressive number of articles published and over 100 successful implementations, the marketing side of the Theory of Constraints is not much discussed. This paper focuses on providing an overview of the Theory of Constraints of the main principles and techiniques, the concept’s implications for marketing and illustrates the suitability of the Theory of Constrainst for marketing management in Estonia with two cases.